2004
DOI: 10.1002/ana.20295
|View full text |Cite
|
Sign up to set email alerts
|

C‐peptide prevents nociceptive sensory neuropathy in type 1 diabetes

Abstract: We examined the effects of C-peptide replacement on unmyelinated fiber function in the hind paw, sural nerve C-fiber morphometry, sciatic nerve neurotrophins, and the expression of neurotrophic receptors and content of neuropeptides in dorsal root ganglia in type 1 diabetic BB/Wor-rats. C-peptide replacement from onset of diabetes had no effect on hyperglycemia, but it significantly prevented progressive thermal hyperalgesia and prevented C-fiber atrophy, degeneration, and loss. These findings were associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 62 publications
6
94
0
Order By: Relevance
“…Thermal plantar test. Latencies of hind paw withdrawal to thermal stimulation (42°C; 152 mW/cm 2 ) were used as measures of thermal hyperalgesia and were measured at 4 and 7 months using a UGO Biological Research apparatus (Comerio, Italy) (11,12). The time from heat source activation to the animal's self-withdrawal in seconds was measured six times in alternating hind paws.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal plantar test. Latencies of hind paw withdrawal to thermal stimulation (42°C; 152 mW/cm 2 ) were used as measures of thermal hyperalgesia and were measured at 4 and 7 months using a UGO Biological Research apparatus (Comerio, Italy) (11,12). The time from heat source activation to the animal's self-withdrawal in seconds was measured six times in alternating hind paws.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we have demonstrated a relationship between impaired insulin action and suppressed neurotrophic support, decreased expression of nociceptive neuropeptides, and degeneration of their parent dorsal root ganglion (DRG) cells (11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental studies have investigated direct insulin signaling of sensory neurons in diabetic or injury models (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39): the administration of local lowdose subhypoglycemic near nerve insulin reversed ipsilateral slowing of motor conduction velocity in diabetic rats without lowering plasma glucose levels. The local injections of insulin have no impact on changes of neuropathy in other territories of the same rat (contralateral side given carrier or in the caudal nerve) (27).…”
Section: Pathogenesismentioning
confidence: 99%
“…A novel prospect is the possibility to administer insulin intranasally, an approach that can access the cerebrospinal fluid and has been used to treat other neurological conditions (29). Insulin is related to insulin-like growth factors in that they can cross-occupy each other's receptors and share downstream survival transduction pathways (32)(33)(34)(35).…”
Section: Pathogenesismentioning
confidence: 99%